THE RELATIONSHIPS IN THE SYSTEM OF FORMAL AND INFORMAL INSTITUTIONS IN THE TRANSFORMATION OF AGRARIAN RELATIONS IN THE RUSSIAN ECONOMY - Tatyana P. Maximova (Статистика и экономика)
The article substantiates the need for institutional methodology in the study of the transformation of agrarian relations in the Russian economy, the main directions of the institutional methodology in modern conditions. Special attention is paid to the use of the content of theoretical studies D. Norton to explain the features of the evolution of agrarian relations in the national economy. Special attention is paid to the role and importance of informal institutions in the agricultural sector of the economy; emphasis on together complements and contradictions of the new established informal and formal institutions, including their features in the system of agrarian relations of the Russian economy.